Technical and clinical assessment of oxygen concentrators. Issue 11 (November 1985) - Gould, G A; Scott, W; Hayhurst, M D; Flenley, D C
Abstract : One membrane oxygen enricher (Oxygen Enrichment Company OE-4E) and four molecular sieve (MS) concentrators (Mountain Medical Econo2, De Vilbiss MINI DeVO2, Cryogenic Roomate III, and Mountain Medical Mini O2) have been studied to assess technical and clinical performance. During four weeks of continuous operation at a flow rate of 2 l min-1 (6 l min-1 for OE-4E) consistent oxygen levels were delivered by all machines (mean greater than 93% for MS concentrators, 36.5% for OE-4E). At flow rates of up to 21 mm-1 all four MS machines delivered oxygen concentrations greater than 92%, but at 3 l min-1 (Econo2 89.6%, MINI DeVO2 93.9%, Roomate III 92.0%, Mini O2 85.0%) and at 4 l min-1 (Econo2 78.0%, Mini DeVO2 84.7%, Roomate III 83.3%, Mini O2 69.1%) the two newer machines gave higher oxygen concentrations. In 20 hypoxic patients the mean oxygen saturation levels achieved when they were breathing oxygen from the MS concentrators at a flow rate of 2 l min-1 were similar (Econo2 92.6%, MINI DeVO2 92.5%, Roomate II 92.6%), but the level achieved when they were breathing from the OE-4E, at the equivalent flow rate of 6 l min-1, was lower (91.0%, p less than 0.005). The performance of concentrators in service (Econo2, MINI DeVO2, Mini O2) was satisfactory when judged by patients' oxygen saturation levels and delivered oxygen concentrations. The OE-4E may be indicated for a small number of patients who require oxygen with high humidification. The four MS concentrators studied are all suitable for domiciliary use, but the MINI DeVO2 and Roomate III have advantages in terms of better performance at high flow rates and reduced size and weight.